QUALITATIVE STUDY OF LOCAL CULTURAL WISDOM AND HEALTH SERVICES ON STUNTING EVENTS - Sutarto (Indonesian Journal of Medical Anthropology, 2022)
Preliminary. Stunting is a condition of chronic malnutrition accompanied by complications of the disease. The prevalence of stunting in children under five in Indonesia and the province of Lampung is still high and the highest is in rural areas. Stunting occurs from the initial nutritional status of the mother before pregnancy, during pregnancy and this condition is thought to be influenced by local habits in attitudes and behavior in the care of pregnant women with their babies. Cipadang village is one of the villages formed from immigration from Java to Sumatra, which makes this village inhabited by the majority of the population of Javanese ethnicity with their cultural style. Socio-cultural conditions in general affect the health of mothers during pregnancy and the pattern of child rearing when they are under 2 years old. The purpose of this study is to explain the state of local culture and health services on the incidence of stunting. Method. This study uses a qualitative approach, to explore in depth the socio-cultural and health services related to the incidence of stunting. Sources of information came from informants, 17 people through focus group discussions. Results and Discussion. The research location village is inhabited by the majority of the population of Javanese ethnicity with its cultural style, with an agricultural livelihood. The characteristics consist of 14 mothers of toddlers and 2 posyandu cadres in Cipadang village, 1 community leader with an age range of informants between 21 to 45 years with the most education level being Elementary School. The community pays special attention to the period of pregnancy, and there are habits in the care of babies, pregnant women and postpartum mothers with ancestral traditions. However, this habit has begun to shift to health care services. Knowledge of general informants is good but behavior is not in accordance with health standards. Conclusion. Some cultures still have an influence, there are habits in caring for babies, pregnant women and postpartum mothers. Good knowledge has not been able to describe the desired behavior